FINAL REPORT AND RECOMMENDATIONS FROM THE HEALTH COMMUNITY TO THE 101ST CONGRESS AND THE BUSH ADMINISTRATION ON THE OCCASION OF THE 25TH ANNIVERSARY OF THE SURGEON GENERAL'S FIRST REPORT ON SMOKING - ANDREWS,MA; BALLIN,S; BLAKEMAN,EM; CONNOLLY,GN; CRANE,M; DURBIN,RJ; ENGLEBERG,AL; HOLLAR,J; KELLIE,SE; KENDALL,D; LEMAISTRE,C; LIGHTFOOT,S; MYERS,M; PAINTER,J; PINNEY,JM; SHEPHERD,PL; SLADE,J; SYNAR,M; WARNER,KE (Tufts Archival Research Center, 2007)
Report prepared by the University of Texas Medical Center in Houston Texas. Provides information on several issues pertaining to tobacco and the Tobacco Industry. Includes reports on nicotine addiction, advertising targeted at specific populations, U.S. policy concerning tobacco, lobbying and the international tobacco market among others. Suggests ways to deal with the issue at the end of each individual report.